Shielding of electromagnetic waves at microwave frequencies with the split-ring resonator metamaterial - Sanchez, Laureano M.; Boggi, Silvina; Fano, Walter G. (My University, 2024)
In this work, the shielding efficiency of a split ring resonator (SRR) formed by a periodic structure built from concentric copper rings printed on a dielectric material has been studied. These artificial materials called metamaterials can be represented as a homogeneous material that has effective constitutive parameters that could not be obtained from naturally occurring materials, such as magnetic permeability and electrical permittivity simultaneously negative. Simulations of the effective magnetic permeability of the material were performed by varying the geometry of the metamaterial. This analysis enables the design and construction of structures with properties that make them an attractive candidate for shielding applications in the range of microwave frequencies. This material is an alternative to massive metallic materials and can lower costs in electromagnetic absorbers. The metamaterial has been built with 100 unit cells on each dielectric slab, stacking 5 slabs. We have made experimental measurements of the shielding effectiveness of these materials when subjected to an electromagnetic plane wave with a magnetic field polarized in the direction perpendicular to the dielectric slabs. Index Terms—metamateriales, resonador de anillo dividido, permeabilidad magnética, eficiencia de blindaje´
Keywords: metamaterials; split ring resonator; magnetic permeability; shielding efficiency